Perbandingan Penyelesaian Sengketa Tata Usaha Negara Melalui PTUN dan Ombudsman - Asti Anindya Khoerunisa; Tiara Kansa Anjar Pratiwi; Firman Khaidar Ahmad Dimyati; Aksa Maraditia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the differences between the functions of the State Administrative Court (PTUN) and the Ombudsman in resolving State Administrative disputes, examine the scope of authority of both institutions, and assess their effectiveness in providing legal protection to the public. This research employs a normative legal research method using statutory, juridical, and conceptual approaches. The findings indicate that PTUN functions as a judicial institution that resolves State Administrative disputes through litigation mechanisms and issues legally binding and enforceable decisions. In contrast, the Ombudsman serves as a public service supervisory institution that focuses on preventing and addressing maladministration through non-litigation mechanisms, including complaint examination, investigation, mediation, and the issuance of recommendations. In terms of effectiveness, PTUN is more effective in ensuring legal certainty and annulling unlawful State Administrative Decisions, whereas the Ombudsman is more effective in addressing maladministration in public services due to its faster, simpler, and cost-free procedures. These findings demonstrate that both institutions play complementary roles in strengthening legal protection and promoting good governance in Indonesia.